Protein Conformation Changes on Block Copolymer Surfaces Detected by Antibody-Functionalized AFM Tips - Palacio, Manuel L. B. (J Biomed Mater Res A, 2011)
Conformational changes of fibronectin deposited on poly(methyl methacrylate) and poly(acrylic acid) block copolymers with identical chemical compositions were detected using an antibody-functionalized atomic force microscope (AFM) tip. Based on the antibody-protein adhesive force maps and phase imaging, it was found that the nanomorphology of the triblock copolymer is conducive to the exposure of the arginine-glycine-aspartic acid (RGD) groups in fibronectin. For the first time, X-ray photoelectron spectroscopy (XPS) was used to elucidate surface chemical composition and confirm AFM results. The findings demonstrate that block copolymer nanomorphology can be used to regulate protein conformation and potentially cellular response.